The influence of ethical climate on workplace deviant behavior with workplace sprituality as a mediation - Velia Oktavia; Sulastri Sulastri (Universitas Negeri Padang, 2022)
This research has purpose to analyzed: (1) influence of ethical climate on workplace deviant behaviors at the Tirta Alami Regional Water Company. (2) influence of ethical climate on workplace sprituality at the Tirta Alami Regional Water Company. (3) influence of workplace sprituality on workplace deviant behaviors at the Tirta Alami Regional Water Company. (4) influence of ethical climate on workplace deviant behaviors at the Tirta Alami Regional Water Company through workplace sprituality. This research is classified as a causal research. The population in this study were all employees of Tirta Alami Regional Water Company with a total of 105 people. The sample size is determined using the Slovin formula found as many as 83 respondents and sampling in this study using cluster propotional sampling. Collecting data using questionnaire with Likert scale. The analysis technique used is PLS-SEM analysis. This research found that: (1) ethical climate has a significant negative effect on workplace deviant behaviors on employees of the Tirta Alami Regional Water Company (2) ethical climate has a significant positive effect on workplace sprituality on employees of the TTirta Alami Regional Water Company (3) workplace sprituality does not affect workplace deviant behaviors on employees of the Tirta Alami Regional Water Company (4) workplace sprituality cannot mediate the influence of ethical climate relationships on workplace deviant behaviors on employees of the Tirta Alami Regional Water Company.